AKTIVITAS ANTIOKSIDAN PADA EKSTRAK ETANOL 96% ANGGUR LAUT (Caulerpa racemosa) YANG BERASAL DARI PANTAI CIMANDIRI, KABUPATEN LEBAK-BANTEN - Rini Yanuarti; Pratama Pratama; Maretha Alfiana (Fisheries Product Technology Department, Faculty of Marine Science and Fisheries, Universitas Maritim Raja Ali Haji, 2023)
Seaweed is known to have the ability as an antioxidant, antibacterial, and immunostimulant. Antioxidants are compounds that can inhibit free radical oxidation reactions. This study aimed to determine the antioxidant activity of 96% ethanol extract of sea grapes (C.racemosa). Sea grapes extract (C.racemosa) for extract characteristics (moisture content and ash content), phytochemical analysis, heavy metal test, and antioxidant analysis using the DPPH method. The results of the characteristic test of the extract obtained water content (14.49%) and ash content (0.30%), these values ??did not exceed the standard extract values. The results of the phytochemical analysis showed that 96% ethanol extract of sea grapes (C.racemosa) contained steroid/triterpenoid compounds, flavonoids, saponins, and alkaloids. The levels of heavy metals found were still within safe limits, namely, lead (Pb) (TTD), mercury (Hg) (<0.001 ppm), Arsenic (As) (<0.001 ppm), and Cadmium (Cd) (0.005 ppm). The test results showed that the sea grape (C.racemosa) used was safe and free from heavy metal contamination. The results of antioxidant analysis on 96% ethanol extract of sea grape (C.racemosa) obtained an IC50 value of 237.51 mg/L. The IC50 value for quercetin is 9.52 mg/L. The results of antioxidant analysis on 96% ethanol extract of sea grapes (C.racemosa) were included in the moderate antioxidant range (100-250 mg/L). Sea grapes (C.racemosa) have the potential as a natural antioxidant.